Structured Fruit Cube Snack of BRS Vitoria Grape with Gala Apple: Phenolic Composition and Sensory Attributes - Nishiyama-Hortense, Yara Paula [UNESP]; Olivati, Carolina [UNESP]; Shimizu-Marin, Victoria Diniz [UNESP]; Gonçales, Ana Carolina [UNESP]; Soares Janzantti, Natália [UNESP]; Da Silva, Roberto [UNESP]; Lago-Vanzela, Ellen Silva [UNESP]; Gómez-Alonso, Sergio (MDPI, 2024)
This study developed a structured fruit cube (FC) snack using only natural ingredients, specifically red grape and apple, without hydrocolloids and sucrose. After development, physicochemical characterization and analysis of phenolic compounds (PCs), including anthocyanins, flavonols, and hydroxycinnamic acid derivatives, using HPLC-DAD-ESI-MS/MS, were conducted. Sensory quality was also assessed through an acceptance and sensory profile analysis using the rate-all-that-apply methodology. The results showed that the FC had physicochemical characteristics similar to other structured fruits that use hydrocolloids. Additionally, they presented a complex composition of PCs, predominantly including anthocyanins derived from malvidin (tri-substituted methoxylated anthocyanins), notably cumarylated ones. Flavonols compounds comprised the 3-glucoside series of myricetin, quercetin, laricitrin, kaempferol, isorhamnetin, and syringetin; the 3-galactoside series of myricetin and quercetin; and the 3-glucuronic acid series of myricetin and quercitin, along with rutin. The presence of caftaric acid, coutaric acid, fertaric acid, and p-coumaroyl-glucose was also detected, alongside caffeic acid-O-glucoside 1, caffeic acid-O-glucoside 2, chlorogenic acid, 4-O-p-coumaroylquinic acid, and dicaffeoylquinic acid. In conclusion, the selection of natural ingredients was technologically suitable for obtaining an FC. Despite using conventional drying at 60 °C, the product showed notable concentrations of PCs and also achieved great sensory acceptance.
Keywords: anthocyanins; Brazilian hybrid grape; flavonols; HPLC-DAD-ESI-MSn; hydroxycinnamic acid derivatives; natural snacks; rate-all-that-apply